A PACE Program in Alberta: An Analysis of the Issues - Mukesh Khanal (The School of Public Policy Publications, 2019)
In December 2015, Canada participated in the COP21 Paris meetings, “committed to reducing greenhouse gas emissions, to be a leader in the transition to a low-carbon and climate resilient economy,” and to contribute towards reducing global temperature increases (Barter 2016). In Alberta, the Climate Leadership Plan has a number of key action points, including “putting a price on greenhouse gas emissions … ending pollution from coal-generated electricity by 2030 … developing more renewable energy” (Government of Alberta 2018b). Initiatives in “consumer rebates, supply chain incentives, and innovative financing options” can help achieve the federal and provincial targets (Advanced Energy Center 2016, 10). However, energy efficiency upgrades and renewable energy projects are major undertakings and require significant capital investments. A widely held view by environmental advisors, such as Harrington and Heart (2014), is that loans to finance such capital investments are difficult to obtain from traditional lenders.